2021
DOI: 10.1073/pnas.2100869118
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale experiment finds no evidence that a seismic survey impacts a demersal fish fauna

Abstract: Seismic surveys are used to locate oil and gas reserves below the seabed and can be a major source of noise in marine environments. Their effects on commercial fisheries are a subject of debate, with experimental studies often producing results that are difficult to interpret. We overcame these issues in a large-scale experiment that quantified the impacts of exposure to a commercial seismic source on an assemblage of tropical demersal fishes targeted by commercial fisheries on the North West Shelf of Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The d 13 C ‰ for most species also varied between locations, which suggests that these demersal species are limited in their foraging range (Supplementary Figure 1). Restricted movement of L. sebae was confirmed in a concurrent telemetry study, which showed no dispersal of tagged individuals between the two study locations over a six-month period (Meekan et al, 2021). Other telemetry studies of tropical demersal fishes have also found limited movement, home ranges, and activity spaces of tagged individuals (e.g.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The d 13 C ‰ for most species also varied between locations, which suggests that these demersal species are limited in their foraging range (Supplementary Figure 1). Restricted movement of L. sebae was confirmed in a concurrent telemetry study, which showed no dispersal of tagged individuals between the two study locations over a six-month period (Meekan et al, 2021). Other telemetry studies of tropical demersal fishes have also found limited movement, home ranges, and activity spaces of tagged individuals (e.g.…”
Section: Discussionmentioning
confidence: 58%
“…Samples were collected in the Area 3 Management Zone of the Pilbara Fish Trawl Fishery, located approximately 90 km north of Point Samson, off the Pilbara coast in Western Australia (Figure 1). The area encompasses ≈2,500 km 2 of sloping seabed from 50 m water depth in the south to 80 m in the north, an area that has been a Targeted Fishery Closure (TFC) since 1998 and, due to the distance from shore, experiences negligible recreational fishing (Langlois et al, 2021;Meekan et al, 2021). Area 3 is situated within the middle of the fishery to maximise spillover potential to the areas surrounding it (Langlois et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot assess potential thresholds of harm 31 and mitigate associated risks if we have a poor understanding of what we could be harming and how different species suffer harm. While some international studies have found that seismic surveys have only a limited impact on demersal fish of commercial or recreational interest 32 , such results are not necessarily generalisable elsewhere given the array of heterogeneity across marine environments, both in terms of biota and physical characteristics. Nor can such results be extrapolated to other marine species.…”
Section: Short-term Harms In the Oceanmentioning
confidence: 90%
“…PAM is already used for a multitude of biological applications. Examples include monitoring, characterizing and delineating underwater soundscapes, and investigating aquatic communities (e.g., Desjonquères et al, 2015;Erbe et al, 2015;Menze et al, 2017;Mooney et al, 2020;Stanley et al, 2021); documenting the distribution and migration patterns of the great whales (e.g., Risch et al, 2014;Tsujii et al, 2016;Davis et al, 2020;Warren et al, 2021); characterizing the spatial and temporal responses of fish choruses to environmental drivers like temperature, salinity, lunar phase, tide, and time of sunset (e.g., Barrios, 2004;Rountree et al, 2006;Parsons, 2010;Straight et al, 2015;Rice et al, 2016;McWilliam et al, 2017;Parsons et al, 2016;Karaconstantis et al, 2020;Linke et al, 2020); understanding how animals change their behavior and distribution in response to climate change (Gordon et al, 2018), anthropogenic noise sources (e.g., Thompson et al, 2013;Cerchio et al, 2014;Erbe et al, 2019;Meekan et al, 2021), algal blooms (e.g., Rycyk et al, 2020) and extreme weather events like hurricanes (e.g., Locascio and Mann, 2005;Fandel et al, 2020;Boyd et al, 2021;Schall et al, 2021); understanding how prey change their sound production rates or behaviors with the presence of predators (e.g., Luczkovich and Keusenkothen, 2007;Hughes et al, 2014;Bailey et al, 2019;Burnham and Duffus, 2019); and how noise and propagation conditions can affect communication spaces (e.g.,…”
Section: Introductionmentioning
confidence: 99%